Effect of toothbrushing duration and dentifrice quantity on enamel remineralisation: An in situ randomized clinical trial. (December 2016) - Creeth, J.E.; Kelly, S.A.; González-Cabezas, C.; Karwal, R.; Martinez-Mier, E.A.; Lynch, R.J.M.; Bosma, M.L.; Zero, D.T.
Abstract: Objectives: The influence of toothbrushing duration and dentifrice quantity on fluoride efficacy against dental caries is poorly understood. This study investigated effects of these two oral hygiene factors on enamel remineralisation (measured as surface microhardness recovery [SMHR]), enamel fluoride uptake (EFU), and net acid resistance (NAR) post-remineralisation in a randomized clinical study using an in situ caries model. Methods: Subjects (n = 63) wore their partial dentures holding partially demineralised human enamel specimens and brushed twice-daily for two weeks, following each of five regimens: brushing for 120 or 45 s with 1.5 g of 1150 ppm F (as NaF) dentifrice; for 120 or 45 s with 0.5 g of this dentifrice; and for 120 s with 1.5 g of 250 ppm F (NaF) dentifrice. Results: Comparing brushing for 120 s against brushing for 45 s, SMHR and EFU increased by 20.0% and 26.9% respectively when 1.5 g dentifrice was used; and by 22.8% and 19.9% respectively when 0.5 g dentifrice was used. Comparing brushing with 1.5 g against brushing with 0.5 g dentifrice, SMHR and EFU increased by 35.3% and 51.3% respectively when brushing for 120 s, and by 38.4% and 43.0% respectively when brushing for 45 s. Increasing brushing duration and dentifrice quantity also increased the NAR value. The effects of these two oral hygiene factors on SMHR, EFU, and NAR were statistically significant (p < 0.05 in all cases). Conclusion: Brushing duration and dentifrice quantity have the potential to influence the anti-caries effectiveness of fluoride dentifrices. Study NCT01563172 on ClinicalTrials.gov . Clinical significance: The effect of two key oral hygiene regimen factors – toothbrushing duration and dentifrice quantity – on fluoride's anticaries effectiveness is unclear. This 2-week home-use in situ remineralisation clinical study showed both these factors can influence fluoride bioactivity, and so can potentially affect fluoride's ability to protect against caries.